Information Needs of Smallholder Farmers in Lake Victoria Basin for Enhancing Climate-smart Agricultural Practices - Ajwang, Stephen Oloo; Owoche, Patrick; Mutonyi, Jonathan (International Journal of Computing Sciences Research; Vol 8 (2024): Volume 8, 2024)
Purpose – The purpose of this study was to bridge the awareness gap in agricultural information need and use by farmers to improve information access and utilization for enhanced adoption of Climate Smart Agricultural (CSA) practices. Method – Using a mixed methods approach, the study examined the information needs of smallholder farmers in 5 counties in the Lake Victoria Basin, Kenya. Qualitative and quantitative data were collected from 382 farmers and 20 county directors of agriculture, ICT, meteorology, and crop production. Descriptive and inferential statistics were used to analyze quantitative data while thematic analysis was used on qualitative data. Results – The findings showed that many farmers (82.46%) were aware of the existence of climate change which had reduced sorghum yield to 0.45 t/Ha. Therefore, farmers had initiated sustainable practices including planting different crop varieties (83.51%) and varying planting dates (65.18%). High yield was prevalent among farmers practicing crop rotation (95.1%) while those who practiced mono-cropping achieved low yields. Also, the use of inorganic fertilizers led to higher yields. Farmers who planted early maturing crops had log odds that were 1.647 points higher for being in a higher yield level than farmers who planted late maturing crops. Conclusion – The study has the potential to enhance the adaptive capacity of farmers to climate change using suitable CSA practices based on readily available, accessible, and context-specific information Recommendations – The study recommends that farmers be provided with and/or have access to reliable, actionable, relevant, and timely information that matches their needs to enhance resilience through the adoption of climate-adaptive farming techniques. Implications – These findings contribute to research by recommending context-specific information to help farmers bridge the information gap. The findings may contribute to policy by proposing CSA strategies that involve information-based support to smallholder farmers to implement sustainable farming practices.